2016
DOI: 10.3892/br.2016.631
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Dickkopf-1 and tartrate-resistant acid phosphatase 5b serum levels in preschool children with nephrotic syndrome

Abstract: The aim of the present study was to investigate the changes in the serum Dickkopf-1 (DKK-1) and tartrate-resistant acid phosphatase 5b (TRACP-5b) levels in preschoolers with nephrotic syndrome (NS). A total of 50 preschoolers (3-5 years old) with NS and 20 healthy preschoolers (control group) were enrolled in the prospective single-center study. The patients with NS received glucocorticoid treatment and the control group received no treatment. The levels of serum calcium, phosphorus, TRACP-5b, DKK-1 and 25-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
2
0
4
Order By: Relevance
“…We also classified the patients based on the duration of prednisone treatment and cumulative dosage of prednisone 6 months prior to the treatment. Based on the study by Zhang et al (2016) TRAP 5B serum in healthy children is not significantly different from that in patients with SN initial attack 3 and 6 months after induction. It is indicated that TRAP 5B serum level can turn back to normal level at the time of remission due to the reduction dosage of glucocorticoid and reduction of total protein leakage (Zhang et al 2016).…”
Section: Discussionmentioning
confidence: 85%
“…We also classified the patients based on the duration of prednisone treatment and cumulative dosage of prednisone 6 months prior to the treatment. Based on the study by Zhang et al (2016) TRAP 5B serum in healthy children is not significantly different from that in patients with SN initial attack 3 and 6 months after induction. It is indicated that TRAP 5B serum level can turn back to normal level at the time of remission due to the reduction dosage of glucocorticoid and reduction of total protein leakage (Zhang et al 2016).…”
Section: Discussionmentioning
confidence: 85%
“…Sclerostin and Dkk-1 are powerful negative regulators of osteoblastogenesis. An increase in their levels results in reduced osteoblast differentiation and thus decreased bone formation [ 14 , 35 , 36 , 37 ]. Although the mean values of these markers were comparable in both groups of children, sclerostin concentrations were slightly lower in vegetarians.…”
Section: Discussionmentioning
confidence: 99%
“…TRACP5b wird von Osteoklasten exprimiert und gilt als relevanter Biomarker bei metabolischen und pathologischen Erkrankungen des Knochens, aber auch bei malignen Erkrankungen mit Knochenmetastasen und der chronischen Niereninsuffizienz [3,11,18,23,25,32,36,39]. Zusätzlich wird das Enzym von aktivierten oder entzündungsfördernden Makrophagen und dendritischen Zellen exprimiert [3,7,11,18,21,23,25].…”
Section: Biochemie Von Tracp5bunclassified
“…Osteosarkome), bei Haarzellleukämie (lysosomale Speicherkrankheit Morbus Gaucher), sekundärem Hyperparathyreoidismus, fortgeschrittener Niereninsuffizienz, nephrotischem Syndrom, rheumatoider Arthritis, Osteopetrose, ankylierender Spondylitis, koronarer Herzkrankheit und bei normal wachsenden Kindern auf [4,6,11,18,21,23,25,32,36,39].…”
Section: The Biomarker Tartrate-resistant Acid Phosphatase 5b (Tracp5b) a Marker Of Bone Metabolism Abstractunclassified
See 1 more Smart Citation